2015
DOI: 10.1111/mmi.13166
|View full text |Cite
|
Sign up to set email alerts
|

The mycobacterial iron‐dependent regulator IdeR induces ferritin (bfrB) by alleviating Lsr2 repression

Abstract: Summary Emerging evidence indicates that precise regulation of iron (Fe) metabolism and maintenance of Fe homeostasis in Mycobacterium tuberculosis (Mtb) are essential for its survival and proliferation in the host. IdeR is a central transcriptional regulator of Mtb genes involved in Fe metabolism. While it is well understood how IdeR functions as a repressor, how it induces transcription of a subset of its targets is still unclear. We investigated the molecular mechanism of IdeR-mediated positive regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 35 publications
(56 reference statements)
0
41
0
Order By: Relevance
“…Earlier studies with MtLsr2 showed that it is a DNA-bridging protein (Chen et al, 2008) that preferentially binds to and regulates A/T-rich regions of the Mtb genome (Gordon et al, 2010). The bridging mode of MtLsr2 has been shown to be involved in repression of the Fe storage gene bfrB under low Fe conditions (Kurthkoti et al, 2015). On the other hand, MtHU is a sequence non-specific DNA-binding protein that condenses DNA into globular, ball-like structures (Ghosh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies with MtLsr2 showed that it is a DNA-bridging protein (Chen et al, 2008) that preferentially binds to and regulates A/T-rich regions of the Mtb genome (Gordon et al, 2010). The bridging mode of MtLsr2 has been shown to be involved in repression of the Fe storage gene bfrB under low Fe conditions (Kurthkoti et al, 2015). On the other hand, MtHU is a sequence non-specific DNA-binding protein that condenses DNA into globular, ball-like structures (Ghosh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that IdeR in the presence of iron bound the promoter DNA of bfrA and bfrB (36). In-depth analysis of the transcriptional regulation of bfrB showed that IdeR exerted its effect by countering the repressor effect of Lsr2, another histone-like DNA-binding protein (67). It was proposed that Lsr2 functioned as a repressor of bfrB transcription under low-iron conditions, but in the presence of iron, Lsr2 was displaced by IdeR-Fe 2ϩ complexes that bound four tandemly placed IdeR boxes in the bfrB promoter, thereby promoting the transcription of bfrB.…”
Section: Toxicity Of Iron: Protective Role Of the Iron Storage Proteimentioning
confidence: 99%
“…425 H-NS-mediated repression can be alleviated through competition for binding to similar 426 sequences by other transcription factors. Equivalent 'counter-silencing' mechanisms 427 have been reported for Lsr2 in the mycobacteria(Kurthkoti et al, 2015). Given that at least a subset of 428 the Lsr2-controlled specialized metabolic clusters are expressed under particular growth conditions in S.429 venezuelae (e.g.…”
mentioning
confidence: 99%